Successful Use of Extracorporeal Life Support and Continuous Renal Replacement Therapy in the Treatment of Cardiogenic Shock Induced by Tumor Lysis Syndrome in a Pediatric Patient With Lymphoma: A Case Report - Wang, Zhulin; Zhang, Fang; Xiang, Long; Yang, Yinyu; Wang, Wei; Li, Biru; Ren, Hong (Frontiers in Medicine, 2022)
The application of extracorporeal membrane lung (ECMO) in the treatment of cardiopulmonary failure in children with malignant tumor has been controversial. At present, there are few reports on the use of ECMO in thetreatment of children with tumor lysis syndrome. This article reports a case of a 9-year-old girl who presented with hyperkalemia and cardiogenic shock. Cardiopulmonary resuscitation was lasted for 1 hour. VA-ECMO was installed at the bedside to provide cardiopulmonary support for patient, combined with continuous renal replacement therapy (CRRT) to improve the internal environment. The girl was finally diagnosed as mature B-cell lymphoma with tumor lysis syndrome. Severe electrolyte disorder led to cardiogenic shock. After the electrolyte imbalance was corrected, the patient's heart function gradually improved, the ECMO was successfully weaned, and the chemotherapy was continued with the support of CRRT. One month after ECMO weaning, the organ function of the child was good and there were no serious complications. This case report provides us with valuable experience in the management of VA-ECMO in tumor children at the aspects of anticoagulant, anti-infection, internal environment maintenance and organ protection related to ECMO. Extracorporeal life support (ECLS) may play a role in the support of cardiopulmonary failure caused by malignant tumors or required treatment in children.